2018
DOI: 10.3389/fmicb.2018.02728
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Viable but Nonculturable Escherichia coli O157:H7 by Low Temperature and Its Resuscitation

Abstract: Viable but non-culturable (VBNC) cells are alive bacteria cells, but lose their culturability in conventional culture media, usually escape detection by the plate count method and pose a serious threat to food safety and public health. Therefore, it is urgent to study the VBNC status, and to provide theoretical basis and scientific basis for food processing and safety control caused by pathogenic microorganisms. In this study, Escherichia coli O157:H7 was induced to the VBNC state at two different temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 29 publications
(33 reference statements)
8
29
0
Order By: Relevance
“…In recent years, the discovery of microbial quorum-sensing systems has provided new hope for studying the regulatory mechanism of drug resistance mechanisms and overcoming drug resistance. The results show that the quorum-sensing system regulates various cellular processes of microorganisms, such as pathogenic gene expression, toxin production and extracellular polysaccharide synthesis, and plays an important regulatory role in the process of drug efflux pumps and the formation of microbial biofilms [38][39][40]. According to different self-inducible molecules, bacterial QS systems are divided into three types.…”
Section: Microbial Quorum Sensing System and Its Regulation Mechanismmentioning
confidence: 99%
“…In recent years, the discovery of microbial quorum-sensing systems has provided new hope for studying the regulatory mechanism of drug resistance mechanisms and overcoming drug resistance. The results show that the quorum-sensing system regulates various cellular processes of microorganisms, such as pathogenic gene expression, toxin production and extracellular polysaccharide synthesis, and plays an important regulatory role in the process of drug efflux pumps and the formation of microbial biofilms [38][39][40]. According to different self-inducible molecules, bacterial QS systems are divided into three types.…”
Section: Microbial Quorum Sensing System and Its Regulation Mechanismmentioning
confidence: 99%
“…Under these conditions, cells can persist for extended periods without division, called dormancy or a viable but non-culturable (VBNC) state. The VBNC state has been defined as a survival strategy, where bacteria cannot grow on routine culture media but are alive and capable of renewing metabolic activity (Zhao et al, 2017;Dong et al, 2020). Recently, Dong et al (2020) demonstrated that cells in the VBNC state go through different changes, including morphological and compositional variations, which allow them to have a higher resistance to chemical and physical stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to various stresses can induce E. coli the VBNC state (Li et al, 2014), including low temperature (Wei and Zhao, 2018;Zhong and Zhao, 2019) and high temperature (Noor, 2015;Bruhn-Olszewska et al, 2018). Escherichia coli O157: H7, a foodborne pathogen of major concern to public health, has been associated with numerous outbreaks of haemorrhagic colitis and haemolytic uremic syndrome worldwide (Vidovic and Korber, 2016).…”
Section: Introductionmentioning
confidence: 99%